The Creative Artist's Legal Guide: Copyright, Trademark and Contracts in Film and Digital Media Production - Seiter, William J.; Seiter, Ellen (Yale University Press, 2012)
In today's complex media environment, aspiring filmmakers and new media artists are as vulnerable as swimmers in shark-infested waters. This user-friendly guide supplies creative artists with the essential legal concepts needed to swim safely with lawyers, agents, executives, and other experts in intellectual property and business law How do I copyright my screenplay? How can I clear rights for my film project? What can I do to avoid legal trouble when I produce my mockumentary? How do I ascertain whether a vintage novel is in the public domain? Is the trademark I've invented for my production company available? What about copyright and trademark rights overseas? If I upload my film to YouTube, do I give up any rights? Bill Seiter and Ellen Seiter answer these questions and countless others while also demystifying the fundamental principles of intellectual property. Clear and thorough, this plain-spoken and practical guide is essential for anyone seeking to navigate the rapidly changing media environment of today.